Linguistic Experiments in the Poetry of Zafar Iqbal - Safdar Ali; Dr. Kanwar Zafar Iqbal (Zaban-o-Adab, 2025)
Zafar Iqbal is one of the most distinctive voices in modern Urdu poetry, particularly known for his bold and innovative linguistic experiments. This study explores the nature and significance of linguistic experimentation in the poetry of Zafar Iqbal, focusing on his creative use of language, syntax, diction, and semantics. Unlike traditional poetic conventions, Zafar Iqbal deliberately disrupts established linguistic norms to generate new meanings and challenge readers’ expectations. His poetry reflects conscious deviations in grammatical structure, unconventional word formation, ironic tone, and semantic ambiguity, which collectively contribute to a fresh poetic sensibility. These linguistic strategies not only redefine poetic expression but also mirror the intellectual restlessness and critical consciousness of modern and postmodern literary discourse. The study argues that Zafar Iqbal’s linguistic experiments play a crucial role in expanding the expressive potential of Urdu poetry and establishing a new relationship between language, meaning, and poetic experience. Through such experimentation, his poetry becomes a site of resistance against stagnation and a dynamic force in the evolution of modern Urdu poetic language.